2024
DOI: 10.1101/2024.04.11.24305670
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CSF proteomic analysis of semorinemab Ph2 trials in prodromal-to-mild (Tauriel) and mild-to-moderate (Lauriet) Alzheimer’s disease identifies distinct trial cell-type specific proteomic signatures

Alyaa M. Abdel-Haleem,
Ellen Casavant,
Balazs Toth
et al.

Abstract: Targeting of tau pathology has long been proposed as a potential therapeutic strategy for Alzheimer`s disease (AD). Semorinemab is a humanized IgG4 monoclonal antibody that binds to all known isoforms of full-length tau with high affinity and specificity. Semorinemab`s safety and efficacy have been studied in two Phase 2 randomized, double-blind, placebo-controlled, parallel-group clinical trials: Tauriel (prodromal-to-mild AD;NCT03289143) and Lauriet (mild-to-moderate AD;NCT03828747). CSF was collected from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…At the transcriptomic level, YKL-40 expression is increased in human AD brains, but not with subjects carrying the loss of function R62H TREM2 variant which reduces microglia activation [19]. Additional evidence of a semorinemab effect on microglia activity comes from proteomic analyses of Tauriel and Lauriet CSF, where the post-treatment proteomic signatures indicated that the proteomic response in Lauriet was likely of microglial origin [20]. Together with the CSF YKL-40 observations, these findings were unexpected because semorinemab was developed on an IgG4 backbone, which has been demonstrated to have lower binding affinity to fragment crystallizable gamma receptor (FcR) and expected to have reduced immune effector function [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the transcriptomic level, YKL-40 expression is increased in human AD brains, but not with subjects carrying the loss of function R62H TREM2 variant which reduces microglia activation [19]. Additional evidence of a semorinemab effect on microglia activity comes from proteomic analyses of Tauriel and Lauriet CSF, where the post-treatment proteomic signatures indicated that the proteomic response in Lauriet was likely of microglial origin [20]. Together with the CSF YKL-40 observations, these findings were unexpected because semorinemab was developed on an IgG4 backbone, which has been demonstrated to have lower binding affinity to fragment crystallizable gamma receptor (FcR) and expected to have reduced immune effector function [21].…”
Section: Discussionmentioning
confidence: 99%
“…It decreases in response to anti-amyloid therapy, is associated with plaque removal [17,24,25], and across our Ph2 studies, baseline levels demonstrate a degree of correlation with metrics of cognition and function. The robust CSF YKL-40 response and the unique enrichment of microglia proteins observed in an analysis of the Lauriet CSF proteome [20] suggest an intriguing possibility that the stabilization of plasma GFAP in Lauriet may be a response to microglia activity stimulated by semorinemab. Since semorinemab has no discernable effect on Tau aggregation, our post hoc discovery of microglia activation and variations in plasma GFAP between the trials presents a scientific hypothesis that this biology may account for the discrepancies observed in the trial outcomes.…”
Section: Discussionmentioning
confidence: 99%